Nutritional status and practice among patients who underwent major surgery in Hospital Universiti Sains Malaysia - Mohd, Rosliana (2014)
Patients who underwent major surgery do not get enough nutrients, have increased rates of complications and mortality than well-nourished patients. The primary objective of postoperative care is restoration of normal gastro intestinal function to allow adequate food intake and rapid recovery. The goal of this descriptive cross-sectional study is to examine the nutritional status and nutritional practice for patients who have undergone major postoperative procedure. This study also examined the association between level of education and the nutritional status and the different types of surgery and the nutritional status of the patients. 41 surgical patients who were hospitalized in the general surgery and the orthopedics surgery wards Hospital USM were recruited in this study using purposive sampling. Data were collected from March 2014 to April 2014 using validated questionnaire and analyzed using SPSS version 20.0 for frequency, percentage, mean, standard deviation and p value. Ethical approval was obtained from Research Ethics Committee (Human), USM. The respondents rated their highest frequency for breakfast, lunch and dinner as rice and noodle (breakfast : 26.8%, Lunch : 92.7%, Dinner : 46.3%). The result shows that the level of education was significantly associated with nutritional status (p<0.00I). Thus, there was no significantly different of types of surgery and the nutritional status (p=78.82). The results show that surgical patients at the ward were not influenced by factors of hospitality. NUTRITIONAL STATUS AND PRACTICE AMONG PATIENTS WHO UNDERWENT MAJOR SURGERY IN HOSPITAL UNIVERSITI SAINS MALAYSIA (HOSPITAL USM) Patients who underwent major surgery do not get enough nutrients, have increased rates of complications and mortality than well-nourished patients. The primary objective of postoperative care is restoration of normal gastro intestinal function to allow adequate food intake and rapid recovery. The goal of this descriptive cross-sectional study is to examine the nutritional status and nutritional practice for patients who have undergone major postoperative procedure. This study also examined the association between level of education and the nutritional status and the different types of surgery and the nutritional status of the patients. Thus caregivers should identify the defect of nursing care, and institute appropriate changes to improve the quality of nursing care in order to promote patients healing process.